Rare presentations of acute appendicitis - Vedamanickam, Pon Rachel (International Surgery Journal, 2019)
Acute appendicitis is the one of the most common emergency conditions that the rural surgeon must deal with. Though the majority of patients present with the typical symptoms of right iliac fossa pain, nausea and anorexia, many patients do present with atypical symptoms and signs. These patients present a challenge to rural surgeons. Acute appendicitis is a great mimic and can present with a variety of symptoms. The eyes don’t see what the mind doesn’t know and it is important to know the various ways in which appendicitis can present and to always keep it as a differential diagnosis while managing a patient with acute abdomen. In this paper we have looked at 4 different presentations of appendicitis. Appendicitis is a great mimic and should always be kept as a differential for acute abdomen.